2002
DOI: 10.1021/es020930d
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Beam Treatment of Aromatic Hydrocarbons That Can Be Air-Stripped from Contaminated Groundwater. 2. Gas-Phase Studies

Abstract: The electron-beam (EB) degradation of volatile aromatics (benzene, toluene, ethylbenzene, xylenes: BTEX) in groundwater strip gas, which in the present work has been modeled by the introduction of the desired aromatic(s) to a stream of air or another gas, such as oxygen, is initiated essentially by the addition of *OH radicals to the aromatic ring, giving rise to hydroxycyclohexadienyl radicals, which form the corresponding peroxyl radicals upon addition of oxygen. As studied in some detail with benzene as a B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Radiolytic processes, especially those associated with the formation of excited molecules, dissociative capture of radicals, and oxidation, can lead to the formation of cleavage products of C–C bonds as well as bonds between a carbon and a heteroatom. Under anaerobic conditions, radiolysis eliminates gaseous fragmentation products such as H 2 , CO 2 , CH 4 , N 2 , etc. , Under aerobic conditions, organic pollutants can undergo sequential cleavages, leading to their complete conversion to CO 2 and H 2 O or, in the presence of heteroatoms, to oxides of the corresponding elements (SI, section S1). Such a process is called mineralization.…”
Section: Combined Application Of Treatment Methodsmentioning
confidence: 99%
“…Radiolytic processes, especially those associated with the formation of excited molecules, dissociative capture of radicals, and oxidation, can lead to the formation of cleavage products of C–C bonds as well as bonds between a carbon and a heteroatom. Under anaerobic conditions, radiolysis eliminates gaseous fragmentation products such as H 2 , CO 2 , CH 4 , N 2 , etc. , Under aerobic conditions, organic pollutants can undergo sequential cleavages, leading to their complete conversion to CO 2 and H 2 O or, in the presence of heteroatoms, to oxides of the corresponding elements (SI, section S1). Such a process is called mineralization.…”
Section: Combined Application Of Treatment Methodsmentioning
confidence: 99%
“…The yields of the monohydroxylated products are significantly lower than G ( • OH) = 5.4 or the G (−Q) = 5.21. Such a discrepancy is not an unusual phenomenon. , In the reaction of • OH with 2‘-deoxyguanosine, the pulse radiolysis studies account for the reactivity of about 80% of the hydroxyl radicals, whereas the final product analysis accounted for only 25% of the hydroxyl radicals . A study of the reactivity of • OH with pyridine reported significantly lower yields of the three isomeric hydroxypyridines following the radiolysis of N 2 O-saturated solutions (0.13 for 3-hydroxypyridine, 0.4 for 2-hydroxypyridine, and 0.20 for 4-hydroxypyridine) .…”
Section: Resultsmentioning
confidence: 99%
“…The oxidation of VOCs in air using EB irradiation has been studied to develop methods for purifying ventilation gases containing dilute VOCs released from paint and chemical synthesis factories/plants [1][2][3][4][5][6][7]. Aromatic hydrocarbons such as toluene and xylene, used widely as paint solvents, are oxidized under EB irradiation into volatile (gaseous) and nonvolatile (particulate) byproducts besides CO 2 and CO (CO x ) [1][2][3][6][7][8]. The byproducts must be oxidized into CO x by further oxidation because they can contribute to photochemical oxidants and SPMs in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%